Computer-Based Test Application to Support E-Learning in Pandemic Situation - Imam Soleh Marifati; Joko Dwi Mulyanto; Chandra Kesuma; Ubaidillah Ubaidillah; Suripah Suripah (LPPM Universitas Islam 45 Bekasi, 2021)
The use of information technology in education is a new breakthrough. During the current COVID-19 pandemic, many teaching and learning activities are carried out online using the internet in the form of e-learning. one important part of e-learning is the test. Computer based test (CBT) can be implemented in schools that should be accessed by students from remote places. Computer-based test applications can be used as a complement to online learning by utilizing the web technology. Web-based applications allows access by students with an internet connection using PC/Laptop or other mobile devices. In addition, implementation costs can be saved because paperless. Computer-based test applications also make it easier for teachers to grade the answer where the application can automatically provide the score instantly when students finish the test. In this study, the application was built using the web technology that run from various devices and platforms. Access applications can be designed for local network use (intranet) or online by hosting the application on a webserver. The application development uses a system development life cycle approach using PHP-MySQL technology. Keyword : CBT, computer base test, PHP-MySQL, webapps.